Standart Sudut Kemiringan Minimal Arah Kiblat Masjid Di Kota Gorontalo - Syafrudin Katili; Asna Usman Dilo (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
The substance of issue in this study is how many (degrees) the minimum standardized angle still be considered feasible and how the application which is raised in the title The Minimum Standardized Angle of the Kiblah Direction of Mosques in Gorontalo City, with the aims on trying to find the minimum standardize referred to and to be used as guidelines by the community (Jamaah) whether or not to make row adjustments in the mosques that experienced irregularities of kiblah direction. Based on early studies showed that mostly the mosques of Gorontalo city deviate from 1 to 15 degrees from the true direction of Kiblah. With the approach of science and technology especially in the field of astronomy (falak), then what is desired by the provisions of Islamic law ( syari) above can be well realized. Deviations of Kiblah direction of mosques in Gorontalo City today still can be find the solution to make rows improvements / adjustments in the mosques to the true direction of Kiblah or at least meet the minimum standardized angle which can be considered feasible in terms of the direction of kiblah in the mosques has not been out of boundary areas of the city of Mecca.